Novel anti-EGFR scFv human antibody-conjugated immunoliposomes enhance chemotherapeutic efficacy in squamous cell carcinoma of head and neck. (July 2020) - Wang, Yi-Ping; Liu, I.-Ju; Chung, Meng-Jhe; Wu, Han-Chung
Highlights: Chemotherapy is often required to control squamous cell carcinoma of head and neck. Immunoliposome (IL) specifically deliver therapeutic payload through passive and active targeting. EGFR-targeting IL enhanced endocytosis and reduced the IC50 of payloads significantly. EGFR-targeting IL induced faster tumor suppression without additional side effects. EGFR-targeting IL significantly prolonged median survival time in murine models. Abstract: Background and objectives: Squamous cell carcinoma of head and neck (SCCHN) is the fifth most prevalent cancer worldwide. Because the anatomical complexity of this region, complete surgical resection is often not achievable and conventional chemotherapy would aid locoregional control and mitigate distant metastasis. Nonetheless, the nonspecific cytotoxicity and short in vivo half-life of conventional chemotherapeutic drugs limit their effects. Given the high frequency of overexpression of wild type epidermal growth factor receptor (EGFR), we exploit EGFR as a homing beacon for drug delivery system with cytotoxic payloads. Materials and methods: We generated fully human anti-EGFR single chain variable fragment (scFv)-conjugated immunoliposomes (IL) containing doxorubicin and vinorelbine and tested their anti-neoplastic efficacy in vitro and in vivo . Result: Our IL enhanced endocytosis and significantly reduced the half maximal inhibitory concentrations of the therapeutic payloads when compared to non-targeting liposomal counterparts in various cell lines of SCCHN. Furthermore, median survival time was significantly prolonged in subcutaneous and orthotopic SCCHN xenograft murine models treated with our IL formulations than those treated with non-targeting counterparts (94 days versus 60 days and 72 days versus 56 days, respectively) without evident increased systemic toxicity. Conclusion: The therapeutic index of the chemotherapeutic payloads was augmented by our EFGR-targeting IL formulation and they are warranted for further development and preclinical trial.